De la réparation à la restauration - Céline Granjou; Stéphanie Gaucherand; Elaine Chanteloup (Revue de Géographie Alpine)
In this article, we analysed how the objectives behind the revegetation of ski trails have evolved since the 1970’s. Our approach was based on a sociological survey. We show that the revegetation was first launched in order to repair the scars due to the works and to the infrastructures on the resort and then became, over time, a more complex restoration project. At first, revegetation techniques were developed to fight ground erosion. Soon, it was also associated with the idea of “turning the mountain green again”. Now, 40 years later, it aims at restoring both a natural ecosystem and a cultural landscape. The ski resort’s managers, the technicians, the farmers, and the concerned researchers share a common wish for autochthony, which sometimes is close to folklorisation. Far from an ethical and general perspective, this study suggests that the physical characteristics of the territory, its specific history and its actors’ configuration shape the way ecological restoration is locally performed through political choices and technical decisions, as well as the debates which are at stake. As a conclusion, we point the specificity of our results concerning l’Alpe d’Huez and discuss their validity for other alpine ski resorts.